PENATALAKSANAAN FISIOTERAPI PADA KASUS OSTEOARTHRITIS GENU DEXTRA DI RUMAH SAKIT KRAKATAU MEDIKA - Ikhlasinufus (Poltekkes 'Aisyiyah Banten, 2022)
Background: Osteoarthritis is also known as calcification of the joints. The main disorder of osteoarthritis is the breakdown of joint cartilage. Joint cartilage is a joint component that lines the ends of bones in joints, functions as a cushion and shock absorber when two bones collide when the joint is moved (1) Complaints of joint pain usually come and go and attack only a few joints. In the early stages, joint pain occurs after strenuous physical exercise and then disappears after rest. The complaint then progresses to joint stiffness when you wake up in the morning which disappears within 15-30 minutes and decreases after being moved (2). Objective: to determine the management of physiotherapy in the condition of genu dextra osteoarthritis at the Krakatau medika hospital. Method: quantitative research with cross sectional design. Measurement of research variables was only done once by observation. Results: The patient did the examination, there was motion pain in the right knee joint, limited right knee LGS, decreased muscle strength. Parameters used to evaluate pain using a vase, LGS with Goneo Meter, muscle strength with MMT. Patients have difficulty walking long distances, squatting to standing, for toileting, limited range of motion, decreased muscle strength. In this case the management given is MWD, Tens, exercise therapy (isometric exercise, Hold Relax). Conclusion: Giving these three modalities greatly affects the condition of knee osteoarthritis, which can help prevent and treat problems such as:1. reduce pain in the knee starting from tenderness and movement using the VDS scale, 2. increasing the range of motion of the joint with a goneometer, 3. increasing muscle strength with MMT, 4. increasing the patient's functional activity with the jette scale. Suggestion: Physiotherapists are advised to always try to improve knowledge so as to identify problems that can arise in patients and can perform appropriate physiotherapy interventions for successful therapy.